“Pornography Encouraged Me to Belittle Women”: A Thematic Analysis of Men's Reflections on Violence Against Women and Ceasing Pornography Use - Jovanovski, Natalie (Violence against women, 2023)
Within a context of increasingly ubiquitous pornography consumption among men, little is known about men who reject pornography, their motivations to stop consuming it, and their concerns about the treatment of women. In this article, we explore the stated motivations of 124 men who have decided to stop consuming pornography, in order to understand what role—if any—concerns about violence against women and gender equality played in their decision. Specifically, we focus on the implications of these findings for future research on the role of men in preventing or addressing harmful attitudes about women through their everyday practices.